Resin composition and method for producing the same, and molded body and gear

A resin composition combining aromatic polysulfone with specific polar group content and a fluororesin enhances fatigue resistance, addressing the limitations of conventional resin compositions in mechanical parts by improving mechanical durability through stress dispersion.

JP2025007207APending Publication Date: 2025-01-17SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023108457
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional resin compositions and molded products, such as those containing aromatic polysulfone, lack sufficient fatigue resistance, especially in mechanical parts that experience continuous or periodic force application.

Method used

A resin composition comprising aromatic polysulfone with specific polar group content and a fluororesin with controlled group content, combined with a thermoplastic resin, to enhance fatigue resistance.

Benefits of technology

The resin composition exhibits significantly improved fatigue resistance, as demonstrated by enhanced performance in fatigue tests, with the aromatic polysulfone and fluororesin combination effectively dispersing stress and improving mechanical durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007207000007
    Figure 2025007207000007
  • Figure 2025007207000008
    Figure 2025007207000008
  • Figure 2025007207000001
    Figure 2025007207000001
Patent Text Reader

Abstract

To provide a resin composition which enables provision of a molded body that contains aromatic polysulfone and is excellent in fatigue resistance, and a molded body of the same.SOLUTION: A resin composition contains aromatic polysulfone (A) having a polar group and / or its salt in the molecule, a fluororesin (B), and a thermoplastic resin (C) other than the aromatic polysulfone (A) and the fluororesin (B), wherein a content of the polar group and / or its salt of the aromatic polysulfone (A) is 1×10-5 mol / g or more and 40×10-5 mol / g or less per 1 g of the aromatic polysulfone (A), and a CF3 group content measured by a method for measuring the CF3 group content is less than 0.15%. A method for measuring CF3 group content: determining CF3 group content by a following expression (f1), from a peak area ICF3 corresponding to a CF3 group and a peak area ICF2 corresponding to a CF2, which are measured by 19F solid NMR. CF3 group content (%)={((ICF3) / 3) / ((ICF2) / 2)}×100(f1).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a production method thereof, as well as a molded article and a gear. [Background technology]

[0002] Aromatic polysulfone is used in various applications as a molding material for molded articles because of its excellent heat resistance and chemical resistance. Patent Document 1 discloses a resin composition containing aromatic polysulfone for use as a sliding material. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5564986 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there has been a study on replacing metal parts that have been conventionally used as machine parts with resin molded bodies. Among machine parts, parts such as gears that are subjected to continuous or cyclical force for a long period of time require fatigue resistance. However, in the conventional resin composition and molded article thereof as described in Patent Document 1, there is still room for improvement in terms of fatigue resistance.

[0005] The present invention has been made in order to solve the above-mentioned problems, and has an object to provide a resin composition that contains aromatic polysulfone and is capable of providing a molded article having excellent fatigue resistance, and a molded article made from the resin composition. Another object of the present invention is to provide a gear which contains aromatic polysulfone and has excellent fatigue resistance. [Means for solving the problem]

[0006] As a result of intensive research aimed at solving the above problems, the present inventors have discovered a method for producing an aromatic polysulfone (A) having a polar group and / or a salt thereof that satisfies a specific content, and a CF 3 The present inventors have found that a molded article of a resin composition containing a fluororesin (B) having a specific group content exhibits excellent fatigue resistance, which has led to the completion of the present invention. That is, the present invention has the following aspects.

[0007] <1> The present invention comprises an aromatic polysulfone (A) having a polar group and / or a salt thereof in the molecule, a fluororesin (B), and a thermoplastic resin (C) other than the aromatic polysulfone (A) and the fluororesin (B), wherein the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the fluororesin (B) has the following <CF 3 Measurement method for the content of CF 3 The resin composition has a group content of less than 0.15%. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Group content (%)={((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

[0008] <2> The thermoplastic resin (C) is an aromatic polysulfone (c) other than the aromatic polysulfone (A). <1> The resin composition according to claim 1. <3> The aromatic polysulfone (c) has a repeating unit represented by the following formula (1): <2> The resin composition according to claim 1. (1)-Ph 1 -SO 2 -Ph 2 -O- [In the formula, Ph 1 and Ph 2 each independently represents a phenylene group. A hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group, a halogen atom, a sulfo group, a nitro group, an amino group, a carboxyl group, or a hydroxyl group.

[0009] <4> The polar group of the aromatic polysulfone (A) is a hydroxyl group and / or an amino group. <1> ~ <3> 10. The resin composition according to claim 9 . <5> The aromatic polysulfone (A) has a repeating unit represented by the following formula (1): <1> ~ <4> 10. The resin composition according to claim 9 . (1)-Ph 1 -SO 2 -Ph 2 -O- [In the formula, Ph 1 and Ph 2 each independently represents a phenylene group. A hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group, a halogen atom, a sulfo group, a nitro group, an amino group, a carboxyl group, or a hydroxyl group.

[0010] <6> In the fluororesin (B), <CF 3 Measurement method for the content of CF 3 The content of the group is 0.11% or less. <1> ~ <5> 10. The resin composition according to claim 9 . <7> The fluororesin (B) is polytetrafluoroethylene (PTFE). <1> ~ <6> 10. The resin composition according to claim 9 .

[0011] <8> The content of the aromatic polysulfone (A) is 1% by mass or more and 18% by mass or less, and the content of the fluororesin (B) is 5% by mass or more and 22% by mass or less, relative to 100% by mass of the total mass of the resin composition. <1> ~ <7> 10. The resin composition according to claim 9 . <9> The content of the thermoplastic resin (C) is 60% by mass or more and 94% by mass or less with respect to 100% by mass of the total mass of the resin composition. <1> ~ <8> 10. The resin composition according to claim 9 .

[0012] <10> The above <1> ~ <9> A molded article comprising the resin composition according to any one of claims 1 to 5. <11> The above <1> ~ <9> A gear comprising the resin composition according to any one of the above. <12> The gear is for contact with food. <11> The gear according to claim 1. <13> The gear is for contact with medicines. <11> The gear according to claim 1.

[0013] <14> The above <1> ~ <9> 2. A method for producing a resin composition according to claim 1, comprising the steps of: mixing an aromatic polysulfone (A) having a polar group and / or a salt thereof in the molecule; a fluororesin (B); and a thermoplastic resin (C) other than the aromatic polysulfone (A) and the fluororesin (B); wherein the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the fluororesin (B) has the following <CF 3 Measurement method for the content of CF 3 A method for producing a resin composition having a carboxyl group content of less than 0.15%. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Group content (%)={((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1) Effect of the Invention

[0014] According to the present invention, there can be provided a resin composition which contains an aromatic polysulfone and which can provide a molded article having excellent fatigue resistance, and a molded article made from the resin composition. The present invention also provides a gear containing aromatic polysulfone and having excellent fatigue resistance. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is a plan view of a test piece used in a fatigue test. [Diagram 2] 1 shows SEM images of cross sections of test pieces molded from the resin compositions of Example 2, Comparative Example 2, Comparative Example 4, and Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, embodiments of the resin composition, molded article, and gear of the present invention will be described.

[0017] ≪Resin composition≫ The resin composition of the embodiment includes an aromatic polysulfone (A) having a polar group and / or a salt thereof in the molecule, a fluororesin (B), and a thermoplastic resin (C) other than the aromatic polysulfone (A) and the fluororesin (B), and the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the fluororesin (B) has the following <CF 3 CF determined by the method for measuring the group content 3 The base content is less than 0.15%.

[0018] <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Group content (%)={((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

[0019] An aromatic polysulfone (A) having a polar group and / or a salt thereof that satisfies a specific content, and CF 3 A molded article of a resin composition according to an embodiment containing a fluororesin (B) having a specific group content has improved fatigue resistance compared to a molded article of a resin composition not containing the aromatic polysulfone (A). Hereinafter, the fatigue resistance measured for a molded article containing a resin composition of the embodiment may be simply referred to as the fatigue resistance of the resin composition.

[0020] As shown in the examples below, the inclusion of aromatic polysulfone (A) in the resin composition improves the fatigue resistance of the resin composition. However, as shown in the examples below, such an effect of improving fatigue resistance is not observed when the fluororesin is the above-mentioned specific CF 3 When the base content is not satisfied, the difference is not significant.

[0021] That is, the resin composition is a composition comprising an aromatic polysulfone (A) having a polar group and / or a salt thereof that satisfies a specific content, and a CF 3 By containing these in a specific combination with the fluororesin (B) having a specific group content, the fatigue resistance of the resin composition is significantly improved.

[0022] Hereinafter, the content of the polar group and / or its salt is 1×10 per 1 g of the aromatic polysulfone (A). -5 mol / g or more 40×10 -5 The aromatic polysulfone having a molecular weight of 1.0 mol / g or less may be simply referred to as aromatic polysulfone (A). In addition, the CF 3 A fluororesin having a group content of less than 0.15% may be simply referred to as fluororesin (B).

[0023] The resin composition of the embodiment further contains a thermoplastic resin (C). The thermoplastic resin (C) is a thermoplastic resin that does not fall under the category of the aromatic polysulfone (A) and the fluororesin (B).

[0024] The thermoplastic resin (C) is preferably an aromatic polysulfone. Hereinafter, when the thermoplastic resin (C) is an aromatic polysulfone, the content of the polar group and / or its salt per 1 g of the aromatic polysulfone is 1×10 -5 mol / g or more 40×10 -5 The aromatic polysulfone having a polar group and / or a salt thereof content of 1×10 mol / g or less per 1 g of aromatic polysulfone is defined as aromatic polysulfone (A). -5 The aromatic polysulfone having a molecular weight of less than 1.0 mol / g is defined as aromatic polysulfone (c) (in this case, aromatic polysulfone (c) corresponds to thermoplastic resin (C)).

[0025] The resin composition of the embodiment can be obtained by blending the aromatic polysulfone (A), the fluororesin (B), the thermoplastic resin (C), and optional components used as necessary such that the total content (mass %) of those in the resin composition does not exceed 100 mass % of the total mass of the resin composition.

[0026] The aromatic polysulfone (A), the fluororesin (B), and the thermoplastic resin (C) contained in the resin composition of the embodiment will be described below. In addition, each component that may be blended into the resin composition of the embodiment as necessary will be described.

[0027] <Aromatic polysulfone (A)> In this specification, the term "aromatic polysulfone" refers to a compound having a divalent aromatic group (a residue obtained by removing two hydrogen atoms bonded to an aromatic ring from an aromatic compound), an ether bond (-O-), and a sulfonyl group (-SO 2 -) is a resin having a repeating unit containing the following:

[0028] The aromatic polysulfone (A) blended in the resin composition of the embodiment has a polar group and / or a salt thereof in its molecule.

[0029] The salt of the polar group may be composed of, for example, an anion portion formed by dissociating a proton from the polar group and a counter cation, or may be composed of a cation portion formed by adding a proton to the polar group and a counter anion. Examples of the counter cation include alkali metal ions such as lithium ion, sodium ion, and potassium ion, alkaline earth metal ions such as magnesium ion and calcium ion, and ammonium ions and quaternary ammonium ions formed by protonating ammonia or primary to tertiary amines. When the counter cation is a polyvalent cation such as an alkaline earth metal ion, the counter anion may be composed of a plurality of oxyanion groups, or may be composed of an oxyanion group and another anion such as a chloride ion or a hydroxide ion. Examples of the counter anion include a halide ion, a hydroxide ion, a nitrate ion, a sulfate ion, a carbonate ion, and a hydrogen carbonate ion.

[0030] The polar group and / or salt thereof may be located at a main chain terminal of the aromatic polysulfone (A), i.e., the aromatic polysulfone (A) may have at least one terminal polar group and / or salt thereof at the main chain terminal of the aromatic polysulfone.

[0031] The content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10-5 mol / g or less, and may be 6×10 -5 mol / g or more 35×10 -5 mol / g or less, and may be 8×10 -5 mol / g or more 20×10 -5 It may be mol / g or less. The aromatic polysulfone (A) containing polar groups and / or salts thereof in an amount falling within the above-mentioned numerical range is excellent in improving the fatigue resistance.

[0032] The content of the polar group and / or the salt thereof in the aromatic polysulfone (A) means the total content of the polar group and the salt of the polar group.

[0033] The polar group of the aromatic polysulfone (A) is preferably a monovalent polar group, more preferably a hydroxyl group and / or an amino group, more preferably a hydroxyl group or an amino group, and more preferably a hydroxyl group.

[0034] In addition, as a method for measuring the content of the polar group and / or a salt thereof when the polar group is a hydroxyl group, the method for measuring the content of the polar group and / or a salt thereof will be described below.

[0035] [Content of polar group and / or its salt: When the polar group is a hydroxyl group] A specified amount of aromatic polysulfone is dissolved in dimethylformamide, and an excess amount of paratoluenesulfonic acid is added. Using a potentiometric titrator, the solution is titrated with 0.05 mol / L potassium methoxide / toluene-methanol solution (volume ratio of toluene:methanol = 8:2) to neutralize the remaining paratoluenesulfonic acid and then the hydroxyl groups are neutralized. The amount (mol) of potassium methoxide required to neutralize the hydroxyl groups is then divided by the specified amount (g) of aromatic polysulfone.

[0036] Next, as a method for measuring the content of the polar group and / or a salt thereof when the polar group is an amino group, a method for measuring the content of the polar group and / or a salt thereof will be described below.

[0037] [Content of polar group and / or its salt: When the polar group is an amino group] Dissolve aromatic polysulfone in a solvent such as deuterated dimethyl sulfoxide, 1 In H-NMR measurements, the peak area ( 1 H NH2 ) and the peak area of ​​the four protons adjacent to the aromatic carbon derived from the structural unit of aromatic polysulfone ( 1 H PES Based on these peak areas, the amino group content is calculated by the following formula (f0). Amino group content (mol / g) ={( 1 H NH2 / 1 H PES )×2} / formula weight of general formula (1) (f0)

[0038] From the viewpoint of excellent heat resistance and chemical resistance, the aromatic polysulfone (A) preferably has a repeating unit represented by the following formula (1) (hereinafter, sometimes referred to as "repeating unit (1)"). In addition to the repeating unit (1), the aromatic polysulfone (A) may further have one or more other repeating units such as a repeating unit represented by the following formula (2) (hereinafter, sometimes referred to as "repeating unit (2)") or a repeating unit represented by the following formula (3) (hereinafter, sometimes referred to as "repeating unit (3)").

[0039] (1)-Ph 1 -SO 2 -Ph 2 -O- [In the formula, Ph 1 and Ph 2 each independently represents a phenylene group. A hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group, a halogen atom, a sulfo group, a nitro group, an amino group, a carboxyl group, or a hydroxyl group.

[0040] (2)-Ph 3 -R-Ph4 -O- [In the formula, Ph 3 and Ph 4 each independently represents a phenylene group. A hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group, a halogen atom, a sulfo group, a nitro group, an amino group, a carboxyl group, or a hydroxyl group. R represents an alkylidene group, an oxygen atom, or a sulfur atom.

[0041] (3)-(Ph 5 ) n -O- [In the formula, Ph 5 represents a phenylene group. Each hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group, a halogen atom, a sulfo group, a nitro group, an amino group, a carboxyl group, or a hydroxyl group. n represents an integer of 1 to 3. When n is 2 or more, a plurality of Ph 5 may be the same or different.

[0042] Ph 1 ~Ph 5 The phenylene group represented by any one of the following formulas may be a p-phenylene group, an m-phenylene group, or an o-phenylene group, but is preferably a p-phenylene group.

[0043] The number of carbon atoms in the alkyl group which may substitute a hydrogen atom in the phenylene group is preferably 1 to 10. Specific examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group.

[0044] The number of carbon atoms in the aryl group which may replace a hydrogen atom in the phenylene group is preferably 6 to 20. Specific examples of the aryl group include a phenyl group, an o-tolyl group, a m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group.

[0045] Examples of the halogen atom which may substitute for a hydrogen atom in the phenylene group include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0046] When hydrogen atoms in the phenylene groups are substituted with these groups, the number of such groups is preferably 2 or less, more preferably 1, independently for each phenylene group. Among the above, it is preferred that the hydrogen atoms in the phenylene group are not substituted.

[0047] The number of carbon atoms in the alkylidene group represented by R is preferably 1 to 5. Specific examples include a methylene group, an ethylidene group, an isopropylidene group, and a 1-butylidene group.

[0048] The aromatic polysulfone preferably contains 50% or more of the repeating unit (1) relative to the total number of all repeating units (100%), more preferably 80% or more, and even more preferably 90% or more, and further preferably contains only the repeating unit (1). The aromatic polysulfone may contain two or more types of repeating units (1) to (3) independently.

[0049] <Manufacturing method> The aromatic polysulfone can be produced, for example, by polycondensing a dihalogenosulfone compound and a dihydroxy compound corresponding to the repeating unit constituting the aromatic polysulfone.

[0050] For example, a resin having a repeating unit (1) can be produced by using a compound represented by the following formula (4) (hereinafter also referred to as "compound (4)") as a dihalogenosulfone compound and a compound represented by the following formula (5) as a dihydroxy compound.

[0051] For example, a resin having repeating units (1) and (2) can be produced by using compound (4) as the dihalogenosulfone compound and a compound represented by the following formula (6) as the dihydroxy compound.

[0052] For example, a resin having repeating units (1) and (3) can be produced by using compound (4) as the dihalogenosulfone compound and a compound represented by the following formula (7) as the dihydroxy compound.

[0053] (4) X 1 -Ph 1 -SO 2 -Ph 2 -X 2 [where, X 1 and X 2 Each independently represents a halogen atom. 1 and Ph 2 has the same meaning as above.]

[0054] (5)HO-Ph 1 -SO 2 -Ph 2 -OH [In the formula, Ph 1 and Ph 2 has the same meaning as above.]

[0055] (6)HO-Ph 3 -R-Ph 4 -OH [In the formula, Ph 3 , Ph 4 and R has the same meaning as above.]

[0056] (7)HO-(Ph 5 ) n -OH [In the formula, Ph 5 and n are as defined above.]

[0057] When the polar group is a hydroxyl group, the OH group in the above formulas (5) to (7) may correspond to the hydroxyl group which may be located at the main chain terminal of the aromatic polysulfone (A).

[0058] Furthermore, when the polar group is an amino group, for example, an aromatic polysulfone having an amino group and / or a salt thereof at the main chain terminal can be produced by polycondensing an aromatic halogenosulfone compound with an amino compound to produce a by-product, a phenoxy terminal or a phenolate terminal, with a halogen terminal in a polycondensation reaction (polycondensation step).

[0059] Aromatic halogeno sulfone compounds The aromatic halogenosulfone compound may be a compound represented by the following general formula (*).

[0060] X 3 -Ph 6 -SO 2 -Ph 7 -(O-Ph 8 -SO 2 -Ph 9 ) n0 -X 4 (*) In formula (*), X 3 and X 4 each independently represents OH or a halogen atom; X 3 and X 4 At least one of is a halogen atom. 6 and Ph 7 is Ph in the above formula (1). 1 and Ph 2 is synonymous with Ph 8 and Ph 9 each independently represents a phenylene group which may have a substituent.

[0061] In the formula (*), n0 is the number of repetitions of the structural unit contained in the compound represented by the general formula (*), and can be, for example, an integer of 0 or more and 2000 or less. X 3 and X 4Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and a chlorine atom is preferable. Examples of the compound represented by the general formula (*) include bis(4-chlorophenyl)sulfone, 4-chlorophenyl-3',4'-dichlorophenylsulfone, and polymerized compounds thereof. The aromatic halogenosulfone compound can be produced by a known method, and commercially available products such as "Sumikaexcel PES3600P" and "Sumikaexcel PES4100P" manufactured by Sumitomo Chemical Co., Ltd. can also be used. As the compound represented by the above general formula (*), a compound represented by the following general formula (*-1) is preferred from the viewpoints of durability and chemical resistance.

[0062] [ka]

[0063] In formula (*-1), X 30 and X 40 is X in the above formula (*) 3 and X 4 is synonymous with. n01 is the number of repetitions of the structural unit and is an integer of 0 to 2000. R 1 and R 2 each independently represents an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 3 to 10 carbon atoms, a phenyl group, or a halogen atom. n1 is an integer of 0 to 4. n2 is an integer of 0 to 4.

[0064] Amino compounds As the amino compound, an amino compound having a phenol structure is preferred from the viewpoint of good reactivity. Examples of the amino compound include 4-aminophenol, 3-aminophenol, 2,4-diaminophenol, 2,5-diaminophenol, 3-aminopropanol, and 4-(2-aminoethyl)phenol. Among the amino compounds, the compounds represented by the following general formula (8) are preferred, and among them, 4-aminophenol or 3-aminophenol is more preferred.

[0065] [ka]

[0066] In formula (8), m is an integer of 1 to 5, preferably an integer of 1 to 3, and more preferably 1.

[0067] The polycondensation in the production of aromatic polysulfone is preferably carried out in a solvent using an alkali metal salt of carbonate. The alkali metal salt of carbonate may be a carbonate, which is a normal salt, a bicarbonate (hydrogen carbonate), which is an acidic salt, or a mixture of the two. As the carbonate, sodium carbonate or potassium carbonate is preferably used, and as the hydrogen carbonate, sodium bicarbonate or potassium bicarbonate is preferably used.

[0068] As the solvent for polycondensation, an organic polar solvent is preferably used, specific examples of which include dimethyl sulfoxide, 1-methyl-2-pyrrolidone, sulfolane (1,1-dioxothiane), 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, dimethyl sulfone, diethyl sulfone, diisopropyl sulfone, and diphenyl sulfone.

[0069] During polycondensation, by adjusting the types of raw materials, the molar ratio of the raw materials, the reaction temperature, etc., it is possible to obtain an aromatic polysulfone (A) having a desired amount of polar groups introduced therein.

[0070] In this embodiment, it is preferable to mix the aromatic halogenosulfone compound and the amino compound so that the molar ratio of the amino compound to the halogen atoms at the terminals of the aromatic halogenosulfone compound (amino compound / halogen atom) is 0.3 or more and less than 1.0. The molar ratio is more preferably 0.6 or more and 0.95 or less, even more preferably more than 0.7 and 0.9 or less, and particularly preferably 0.75 or more and 0.85 or less. When the molar ratio is in the above range, the remaining amount of by-produced phenoxy terminal or phenolate terminal and halogen terminal is small, and the polymerization degree of the obtained aromatic polysulfone (A) can be increased.

[0071] The amount of the alkali metal carbonate used is preferably 0.9 to 1.2, more preferably 0.95 to 1.15, in terms of the molar ratio of the alkali metal to the halogen atom at the end of the aromatic halogeno sulfone compound. The more the amount of the alkali metal carbonate used, the faster the targeted polycondensation proceeds, but if the amount of the alkali metal carbonate used is excessive, the amount of phenoxy end or phenolate end produced as a by-product increases. For this reason, it is preferable that the amount of the alkali metal carbonate used is within the above range.

[0072] In the polycondensation step, an aromatic halogenosulfone compound and an amino compound are dissolved in an organic polar solvent, and an alkali metal salt of carbonate is added to the resulting solution to polycondense the aromatic halogenosulfone compound and the amino compound. Thereafter, the unreacted alkali metal salt of carbonate, the by-produced alkali halide and the organic polar solvent are removed from the reaction mixture obtained in the polycondensation step to obtain an aromatic polysulfone (A).

[0073] The heating temperature during polycondensation is preferably higher than 150° C., more preferably 165° C. or higher, and even more preferably 200° C. to 400° C. When the heating temperature during polycondensation is higher than 150° C., the intended polycondensation proceeds quickly, and therefore the degree of polymerization of the resulting aromatic polysulfone (A) can be increased.

[0074] In the polycondensation step, the temperature is gradually increased while removing the by-produced water, and after the temperature reaches the reflux temperature of the organic polar solvent, the temperature is preferably maintained for 1 hour to 50 hours, more preferably 2 hours to 30 hours. The longer the polycondensation time, the more the desired polycondensation proceeds, and the higher the polymerization degree of the resulting aromatic polysulfone (A) becomes.

[0075] The aromatic polysulfone (A) is obtained by removing the unreacted alkali metal carbonate, the by-produced alkali halide, and the organic polar solvent from the reaction mixture obtained in the polycondensation step. The unreacted alkali metal carbonate and the by-produced alkali halide may be removed by filtration, extraction, centrifugation, or the like before removing the organic polar solvent. The organic polar solvent may be removed by distilling off the organic polar solvent, or by mixing with a poor solvent for aromatic polysulfone to precipitate aromatic polysulfone and separating it by filtration, centrifugation, or the like. Since the unreacted alkali metal carbonate, the by-produced alkali halide, and the organic polar solvent can be simultaneously removed, it is preferable to mix with a poor solvent for aromatic polysulfone that can dissolve the unreacted alkali metal carbonate and the by-produced alkali halide, precipitate aromatic polysulfone, and separate it by filtration, centrifugation, or the like.

[0076] Examples of poor solvents for aromatic polysulfone include methanol, ethanol, 2-propanol, hexane, heptane, and water, with water being preferred because it is easy to remove.

[0077] The reduced viscosity of the aromatic polysulfone (A) can be an index of molecular weight, and is preferably 0.25 dL / g or more, more preferably 0.30 dL / g or more, and even more preferably 0.35 dL / g or more. When the reduced viscosity of the aromatic polysulfone (A) is equal to or higher than the above lower limit, the effect of improving the fatigue resistance by the aromatic polysulfone (A) is more satisfactorily exhibited, which is preferable.

[0078] The upper limit of the reduced viscosity of the aromatic polysulfone (A) is not particularly limited, but may be 0.60 dL / g or less, or may be 0.55 dL / g or less. When the reduced viscosity of the aromatic polysulfone (A) is equal to or less than the above upper limit, it is easy to adjust the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) to a desired value, which is preferable.

[0079] An example of the numerical range of the reduced viscosity of the aromatic polysulfone (A) may be 0.25 dL / g or more and 0.60 dL / g or less, 0.30 dL / g or more and 0.60 dL / g or less, or 0.35 dL / g or more and 0.55 dL / g or less.

[0080] In this specification, the reduced viscosity of the aromatic polysulfone is a value measured by the following method.

[0081] [Reduced viscosity of aromatic polysulfone] First, about 1 g of aromatic polysulfone is precisely weighed and dissolved in N,N-dimethylformamide to a volume of 1 dL, and the viscosity (η) of this solution is measured at 25°C using an Ostwald type viscosity tube. The viscosity (η) of the solvent N,N-dimethylformamide is also measured. 0 ) is measured at 25°C using an Ostwald type viscosity tube. The viscosity of the resulting solution (η) and the viscosity of the solvent (η 0 ) and the specific viscosity ((η-η 0 ) / η 0 The value obtained by dividing the specific viscosity obtained by the concentration of the solution used in the measurement (approximately 1 g / dL) is the reduced viscosity (dL / g) of the aromatic polysulfone.

[0082] From the viewpoint of improving the fatigue resistance of the resin composition, the content ratio of the aromatic polysulfone (A) relative to the total mass (100 mass%) of the resin composition is preferably 0.001 mass% or more, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 1 mass% or more, still more preferably 2 mass% or more, and particularly preferably 3 mass% or more. From the viewpoint of facilitating kneading of the resin composition of the embodiment, the content ratio of the aromatic polysulfone (A) relative to the total mass (100 mass%) of the resin composition is preferably less than 30 mass%, more preferably 20 mass% or less, even more preferably 18 mass% or less, even more preferably 15 mass% or less, and particularly preferably 8 mass% or less. An example of the numerical range of the content of the aromatic polysulfone (A) relative to the total mass (100 mass%) of the resin composition may be 0.001 mass% or more and less than 30 mass%, 0.01 mass% or more and less than 30 mass%, 0.1 mass% or more and 20 mass% or less, 1 mass% or more and 18 mass% or less, 2 mass% or more and 15 mass% or less, 3 mass% or more and 15 mass% or less, or 3 mass% or more and 8 mass% or less.

[0083] <Fluoropolymer (B)> The fluororesin (B) in the resin composition of the present embodiment is the following fluororesin (B): <CF 3 Measurement method for the content of CF 3 The base content is less than 0.15%. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Group content (%)={((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

[0084] In addition, the above CF 3 The peak area of ​​the group content was determined with reference to the contents described in Macromolecules 2001, Vol. 34, pp. 66-75.

[0085] Examples of NMR devices for measuring solid samples include 400 MHz NMR devices (manufactured by JEOL RESONANCE, Bruker, Agilent, Varian, etc.).

[0086] CF 3 Calculate the group content 19 F solid-state NMR measurement is performed, for example, by a single pulse method under the following measurement conditions:

[0087] Spectrometer: JNM-ECZL600G (manufactured by JEOL RESONANCE) Static magnetic field strength: 14.1 Tesla (resonance frequency at 1H: 600MHz) Observed nucleus: 19F (resonance frequency 565MHz) Measurement method: Single pulse method MAS condition: 16kHz (PTFE (Fluon L169J) was also measured at 20kHz) Wait time: 15 seconds Number of measurements: 128 (=27, measurement time approx. 32 minutes) Measurement temperature: Room temperature (actual value 23°C) Reference material: PTFE (set to -122 ppm)

[0088] The fluororesin (B) in the resin composition of the present embodiment is <CF 3 The CF group content in the fluororesin (B) is determined by the method described above. 2 CF vs. group content 3 The group content is less than 0.15%, preferably 0.11% or less, more preferably less than 0.05%, and even more preferably 0.03% or less. The above CF 3 The fluororesin (B) satisfying the value of the group content is excellent in the effect of improving fatigue resistance when combined with the above aromatic polysulfone (A).

[0089] the above <CF 3 The CF group content in the fluororesin (B) is determined by the method described above. 2 CF vs. group content 3The base content may be 0.0005% or more, 0.0008% or more, 0.001% or more, or 0.008% or more.

[0090] the above <CF 3 The CF group content in the fluororesin (B) is determined by the method described above. 2 CF vs. group content 3 As an example of the above-mentioned numerical range of the group content, it may be 0.0005% or more and less than 0.15%, 0.0008% or more and less than 0.11%, 0.001% or more and less than 0.05%, or 0.008% or more and 0.03% or less.

[0091] The fluororesin (B) in the resin composition of this embodiment has a decomposition onset temperature of preferably 450° C. or higher, more preferably 470° C. or higher, and even more preferably 473° C. or higher. Here, the decomposition onset temperature is the temperature at which the weight loss rate becomes 0.1% when the fluororesin (B) is heated from 25°C (room temperature) to 800°C at a temperature increase rate of 10°C / min using a thermogravimetric analyzer (product name: TGA-50, manufactured by Shimadzu Corporation). The upper limit of the decomposition initiation temperature of the fluororesin (B) in the resin composition of this embodiment is not particularly limited, and is, for example, 600° C. or lower. For example, the decomposition temperature of the fluororesin (B) in the resin composition of this embodiment is preferably 450°C or more and 600°C or less, more preferably 470°C or more and 600°C or less, and even more preferably 473°C or more and 600°C or less.

[0092] The number average molecular weight (Mn) of the fluororesin (B) in the resin composition of this embodiment is preferably 100 to 5,000,000, more preferably 200 to 1,000,000, further preferably 300 to 50,000, and particularly preferably 10,000 to 30,000. In this specification, the number average molecular weight (Mn) is the number average molecular weight (Mn) obtained by the method described in J. Appl. Polym. Sci. 1973, 17, 3253. Specifically, it means a value calculated by the following formula (m-1) from the heat of crystallization (ΔHc: cal / g) obtained by using a differential scanning calorimeter (product name: DSC-50, manufactured by Shimadzu Corporation). Here, the heat of crystallization (ΔHc) is the heat amount obtained from the area of ​​the crystallization peak in the DSC curve. Number average molecular weight (Mn)=2.1×10 10 ΔHc -5.16 (m-1)

[0093] When the number average molecular weight (Mn) of the fluororesin (B) in the resin composition of this embodiment is within the above preferred range, the effect of improving fatigue resistance is even more excellent.

[0094] CF of the above-mentioned fluororesin (B) 3 The group content, decomposition onset temperature, and number average molecular weight (Mn) can be controlled by changing the production method of the fluororesin (B). For example, CF of fluororesin (B) 3 The CF group content can be increased by increasing the branch chain of the fluororesin, controlling the polymerization degree of the fluororesin (B), or controlling the mixing ratio of the raw material monomers. 3 It is possible to obtain a fluororesin (B) having a group content of less than 0.15%.

[0095] Specific examples of the fluororesin (B) in the resin composition of this embodiment include polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polychlorotrifluoroethylene (PCTFE), ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride (PVDF), and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (perfluoroalkoxyalkane, PFA).

[0096] Of the above, PTFE is preferred as the fluororesin (B) in the resin composition of this embodiment from the viewpoint of improving thermal stability and fatigue resistance.

[0097] That is, the fluororesin (B) in the resin composition of the present embodiment is <CF 3 The CF group content in PTFE is determined by the method 2 CF vs. group content 3 Preferably, the PTFE has a CF group content of less than 0.15%. 3 More preferred is PTFE having a CF group content of 0.0005% or more and less than 0.15%. 3 More preferred is PTFE having a CF group content of 0.0008% or more and 0.11% or less. 3 More preferably, the PTFE has a CF group content of 0.001% or more and less than 0.05%. 3 PTFE having a group content of 0.008% or more and 0.03% or less is more preferred.

[0098] Furthermore, as the fluororesin (B) in the resin composition of this embodiment, PTFE having a decomposition onset temperature of 450°C or more and 600°C or less is preferable, PTFE having a decomposition onset temperature of 470°C or more and 600°C or less is more preferable, and PTFE having a decomposition onset temperature of 473°C or more and 600°C or less is even more preferable.

[0099] Furthermore, as the fluororesin (B) in the resin composition of this embodiment, PTFE having a number average molecular weight (Mn) of 100 to 5,000,000 is preferable, PTFE having a number average molecular weight (Mn) of 200 to 1,000,000 is more preferable, PTFE having a number average molecular weight of 300 to 50,000 is even more preferable, and PTFE having a number average molecular weight of 10,000 to 30,000 is particularly preferable.

[0100] The fluororesin (B) in the resin composition of the present embodiment may be used either alone or in combination of two or more kinds.

[0101] The content of the fluororesin (B) in the resin composition of the embodiment is preferably 2 mass% or more, more preferably 5 mass% or more, even more preferably 8 mass% or more, and particularly preferably 10 mass% or more, relative to the total mass (100 mass%) of the resin composition. When the content of the fluororesin (B) relative to the total mass of the resin composition is at least the above preferable lower limit, the effect of improving fatigue resistance is more excellent.

[0102] The content of the fluororesin (B) in the resin composition of the embodiment is, from the viewpoint of preventing difficulty in powder feeding and a significant decrease in strength during granulation, preferably 30 mass % or less, more preferably 22 mass % or less, even more preferably 20 mass % or less, and particularly preferably 18 mass % or less, relative to the total mass (100 mass %) of the resin composition.

[0103] An example of the above-mentioned numerical range of the content of the fluororesin (B) in the resin composition of the embodiment may be 2 mass% or more and 30 mass% or less, 5 mass% or more and 22 mass% or less, 8 mass% or more and 20 mass% or less, or 10 mass% or more and 18 mass% or less, relative to the total mass (100 mass%) of the resin composition.

[0104] In addition, the content of the fluororesin (B) in the resin composition of the embodiment is preferably 2 mass% or more, more preferably 5 mass% or more, even more preferably 8 mass% or more, and particularly preferably 10 mass% or more, relative to 100 mass% of the total amount of the aromatic polysulfone (A), the thermoplastic resin (C), and the fluororesin (B). The content of the fluororesin (B) in the resin composition of the embodiment is preferably 30 mass% or less, more preferably 22 mass% or less, even more preferably 20 mass% or less, and particularly preferably 18 mass% or less, relative to 100 mass% of the total amount of the aromatic polysulfone (A), the thermoplastic resin (C), and the fluororesin (B). An example of the above-mentioned numerical range of the content of the fluororesin (B) in the resin composition of the embodiment may be 2 mass% or more and 30 mass% or less, 5 mass% or more and 22 mass% or less, 8 mass% or more and 20 mass% or less, or 10 mass% or more and 18 mass% or less, relative to 100 mass% of the total amount of the aromatic polysulfone (A), the thermoplastic resin (C), and the fluororesin (B).

[0105] In the resin composition of the present embodiment, when PTFE is used as the fluororesin (B), the fluororesin (B) in the resin composition of the present embodiment can be produced, for example, by the following method (production method (i) or (ii)).

[0106] Manufacturing method (i) The production method (i) is a method for producing PTFE by combining emulsion polymerization and suspension polymerization. Specifically, tetrafluoroethylene is polymerized in the presence of a polymerization initiator (a water-soluble peroxide) and an aqueous medium (e.g., deionized high-purity pure water) to produce emulsion particles. The emulsion particles are then aggregated to produce aggregated powder. Next, tetrafluoroethylene is polymerized in the presence of the aggregated powder, the polymerization initiator, and the aqueous medium to produce the above-mentioned CF 3 It is possible to produce PTFE having a group content in the above range.

[0107] Manufacturing method (ii) The process (ii) comprises polymerizing tetrafluoroethylene and at least one optional comonomer in an aqueous polymerization medium. Specifically, tetrafluoroethylene and at least one copolymerizable fluorinated ethylenically unsaturated comonomer (e.g., perfluoro(propyl vinyl ether) (PPVE)) are mixed with a particular dispersant (e.g., perfluoroalkyl (C 4 ~C 16 The above-mentioned CF 3 It is possible to produce PTFE having a group content in the above range. For example, the content of the comonomer in the PTFE is preferably 0.005 mol % to 20 mol %.

[0108] Of the above, the fluororesin (B) in the resin composition of this embodiment is preferably a fluororesin produced by the production method (ii).

[0109] <Thermoplastic resin (C)> The thermoplastic resin (C) is not particularly limited as long as it is a thermoplastic resin that does not fall under the category of the aromatic polysulfone (A) and the fluororesin (B).

[0110] Thermoplastic resins are resins that reversibly undergo softening by heating and solidification by cooling when repeatedly heated and cooled. Thermoplastic resins can be broadly classified into liquid crystalline thermoplastic resins (C1), crystalline thermoplastic resins (C2), and amorphous thermoplastic resins (C3).

[0111] <Liquid crystalline thermoplastic resin (C1)> The liquid crystalline thermoplastic resin (C1) is a resin that exhibits optical anisotropy when melted and forms an anisotropic melt at a temperature of 450°C or less. This optical anisotropy can be confirmed by a normal polarization inspection method using crossed polarizers. The liquid crystalline thermoplastic resin (C1) has a molecular shape that is long and thin, flat, and has a molecular chain with high rigidity along the long chain of the molecule (this molecular chain with high rigidity is usually called a "mesogen group"), and has such a mesogen group in either or both of the polymer main chain and side chain. If higher heat resistance is required, it is preferable that the polymer main chain has a mesogen group.

[0112] Examples of the liquid crystalline thermoplastic resin (C1) include liquid crystalline polyester, liquid crystalline polyester amide, liquid crystalline polyester ether, liquid crystalline polyester carbonate, liquid crystalline polyester imide, and liquid crystalline polyamide. Among them, liquid crystalline polyester, liquid crystalline polyester amide, and liquid crystalline polyamide are preferred in that they can provide a resin molded article with high strength, and liquid crystalline polyester and liquid crystalline polyester amide are preferred in that they can provide a molded article with lower water absorption.

[0113] <Crystalline thermoplastic resin (C2)> Crystalline thermoplastic resin (C2) refers to a resin whose molecular structure contains a mixture of crystalline regions in which long chain-like molecules are regularly arranged, and non-crystalline regions in which they are not regularly arranged. Examples include polyethylene, polypropylene, polyacetal, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), polyimide (PI), polyether ether ketone (PEEK), polyether nitrile (PEN), aliphatic polyamide, semi-aromatic polyamide, and aromatic polyamide.

[0114] <Amorphous thermoplastic resin (C3)> Amorphous thermoplastic resins (C3) are resins that do not substantially have crystalline regions in which long chain molecules are regularly arranged in the molecular structure, but are composed only of amorphous regions in which the molecules are not regularly arranged. Examples of such resins include polysulfone resins, polystyrene, polycarbonate, polyetherimide, and polyamideimide.

[0115] On the other hand, the thermoplastic resin (C) is preferably a polysulfone-based resin since it is believed to have good affinity with the aromatic polysulfone (A).

[0116] In this specification, the term "polysulfone-based resin" refers to a compound having a divalent aromatic group and a sulfonyl group (-SO 2-), which is a resin having a repeating unit containing the repeating unit (1). As the divalent aromatic group, the phenylene group exemplified in the repeating unit (1) is preferable, and the hydrogen atoms in the phenylene group may be independently substituted with an alkyl group, an aryl group, a halogen atom, a sulfo group, a nitro group, an amino group, a carboxyl group, or a hydroxyl group. The polysulfone-based resin can be exemplified by the aromatic polysulfone.

[0117] Among the polysulfone-based resins, the thermoplastic resin (C) is an aromatic polysulfone (c) (containing a divalent aromatic group, an ether bond (-O-), and a sulfonyl group (-SO)) that does not fall under the category of the aromatic polysulfone (A). 2 -)) is preferably a resin having a repeating unit containing

[0118] An example of the resin composition of the present embodiment includes an aromatic polysulfone (A) having a polar group and / or a salt thereof in the molecule, a fluororesin (B), and an aromatic polysulfone (c) other than the aromatic polysulfone (A) and the fluororesin (B), and the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the fluororesin (B) has the following <CF 3 Measurement method for the content of CF 3 An example of such a resin composition is a resin composition having a group content of less than 0.15%. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Group content (%)={((ICF3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

[0119] When the thermoplastic resin (C) is an aromatic polysulfone (c), the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the aromatic polysulfone (c) as the thermoplastic resin (C) not corresponding to the aromatic polysulfone (A) is an aromatic polysulfone (c) having a polar group and / or a salt thereof in a molecule of the aromatic polysulfone (c) of 1×10 -5 The aromatic polysulfone has a molecular weight of less than 100 mol / g.

[0120] The polar group is preferably a hydroxyl group. When the polar group is a hydroxyl group, the content of the hydroxyl group and / or a salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 The aromatic polysulfone (c) as the thermoplastic resin (C) not corresponding to the aromatic polysulfone (A) has a content of hydroxyl groups and / or salts thereof in the molecule of the aromatic polysulfone (c) of 1×10 mol / g or less per 1 g of the aromatic polysulfone (c). -5 It may be an aromatic polysulfone having a molecular weight of less than 100 mol / g.

[0121] The polar group is preferably an amino group. When the polar group is an amino group, the content of the amino group and / or a salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 The aromatic polysulfone (c) as the thermoplastic resin (C) not corresponding to the aromatic polysulfone (A) is an aromatic polysulfone having an amino group and / or a salt thereof in a molecule of the aromatic polysulfone (c) of 1×10 mol / g or less per 1 g of the aromatic polysulfone (c). -5It may be an aromatic polysulfone having a molecular weight of less than 100 mol / g.

[0122] When the thermoplastic resin (C) is an aromatic polysulfone, the content of the polar group and / or the salt thereof in the aromatic polysulfone (c) is 1×10 -5 mol / g or less than 5×10 -6 mol / g or less, and may be 3×10 -6 It may be mol / g or less.

[0123] When the thermoplastic resin (C) is an aromatic polysulfone and the polar group is a hydroxyl group, the content of the hydroxyl group and / or a salt thereof in the aromatic polysulfone (c) is 1×10 -5 mol / g or less than 5×10 -6 mol / g or less, and may be 3×10 -6 It may be mol / g or less.

[0124] When the thermoplastic resin (C) is an aromatic polysulfone and the polar group is an amino group, the content of the amino group and / or its salt in the aromatic polysulfone (c) is 1×10 -5 mol / g or less than 5×10 -6 mol / g or less, and may be 3×10 -6 It may be mol / g or less.

[0125] The combination of the polar group contents (preferably hydroxyl groups and / or amino groups, more preferably hydroxyl groups or amino groups, and even more preferably hydroxyl groups) of the aromatic polysulfone (A) and the aromatic polysulfone (c) is such that the content of the polar group and / or a salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the content of the polar group and / or its salt in the aromatic polysulfone (c) is 1×10 -5mol / g or less, and the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 6×10 -5 mol / g or more 35×10 -5 mol / g or less, and the content of the polar group and / or its salt in the aromatic polysulfone (c) is 5×10 -6 mol / g or less, and the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 8×10 -5 mol / g or more 20×10 -5 mol / g or less, and the content of the polar group and / or its salt in the aromatic polysulfone (c) is 3×10 -6 It may be mol / g or less.

[0126] Similarly, the content of the polar group and / or its salt in the thermoplastic resin (C) is 1×10 -5 mol / g or less, and -6 mol / g or less, and may be 3×10 -6 It may be mol / g or less.

[0127] In the resin composition of the embodiment, the total content of the aromatic polysulfone (A) and the aromatic polysulfone (c) may be 50 mass% or more, 61 mass% or more and 92 mass% or less, or 77 mass% or more and 87 mass% or less, relative to the total mass (100 mass%) of the resin composition.

[0128] The aromatic polysulfone (c) not corresponding to the aromatic polysulfone (A) is preferably at least one selected from the group consisting of polyethersulfone, polysulfone, modified polysulfone, and polyphenylsulfone, more preferably polyethersulfone or polyphenylsulfone, and even more preferably polyethersulfone.

[0129] When the thermoplastic resin (C) is an aromatic polysulfone, examples of the reduced viscosity of the aromatic polysulfone (c) include those similar to those of the aromatic polysulfone (A) explained above. From the viewpoint of further improving the fatigue resistance, the difference between the reduced viscosity of the aromatic polysulfone (c) and that of the aromatic polysulfone (A) is preferably, for example, 0.12 dL / g or less.

[0130] From the viewpoint of heat resistance, the thermoplastic resin (C) is preferably at least one selected from the group consisting of polyethersulfone, polysulfone, modified polysulfone, polyphenylsulfone, liquid crystalline polyester, polyetheretherketone, and semi-aromatic polyamide.

[0131] Among these, the thermoplastic resin (C) is preferably an aromatic polysulfone (c) having the repeating unit (1) as the repeating unit, and more preferably an aromatic polysulfone (c) having only the repeating unit (1) as the repeating unit.

[0132] An especially preferred combination is one in which the aromatic polysulfone (A) is an aromatic polysulfone having the repeating unit (1) as the repeating unit (preferably, an aromatic polysulfone having only the repeating unit (1) as the repeating unit), and the thermoplastic resin (C) is an aromatic polysulfone (c) having the repeating unit (1) as the repeating unit (preferably, an aromatic polysulfone (c) having only the repeating unit (1) as the repeating unit).

[0133] In the resin composition of the embodiment, the mass ratio of the content of the thermoplastic resin (C) to the aromatic polysulfone (A) (thermoplastic resin (C) / aromatic polysulfone (A)) may be, for example, from 1 to 60, from 5 to 50, or from 10 to 20. When such a mass ratio (thermoplastic resin (C) / aromatic polysulfone (A)) is within the above range, fatigue resistance is likely to be improved.

[0134] In the resin composition of the embodiment, the mass ratio of the content of the fluororesin (B) to the aromatic polysulfone (A) (fluororesin (B) / aromatic polysulfone (A)) may be, for example, 0.5 to 20, 1 to 10, or 2 to 5. When such a mass ratio (fluororesin (B) / aromatic polysulfone (A)) is within the above range, fatigue resistance is likely to be improved.

[0135] The content of the thermoplastic resin (C) in the resin composition of the embodiment is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 74 mass% or more, relative to the total mass (100 mass%) of the resin composition. The content of the thermoplastic resin (C) in the resin composition of the embodiment is preferably 94 mass% or less, more preferably 89 mass% or less, and even more preferably 84 mass% or less, relative to the total mass (100 mass%) of the resin composition. An example of the above-mentioned numerical range of the content of the thermoplastic resin (C) in the resin composition of the embodiment may be 60 mass% or more and 94 mass% or less, 70 mass% or more and 89 mass% or less, or 74 mass% or more and 84 mass% or less, relative to the total mass (100 mass%) of the resin composition.

[0136] In the resin composition of the embodiment, the content ratio of the aromatic polysulfone (A) and the fluororesin (B) exemplified above can be freely combined. As an example of the resin composition of the embodiment, a resin composition is exemplified in which the content of the aromatic polysulfone (A) is 1 mass% or more and 18 mass% or less, and the content of the fluororesin (B) is 5 mass% or more and 22 mass% or less, relative to 100 mass% of the total mass of the resin composition.

[0137] In the resin composition of the embodiment, the content ratios of the aromatic polysulfone (A), the fluororesin (B), and the thermoplastic resin (C) exemplified above can be freely combined. As an example of a resin composition of an embodiment, the resin composition may preferably contain 1 mass% or more and 18 mass% or less of aromatic polysulfone (A), 5 mass% or more and 22 mass% or less of fluororesin (B), and 60 mass% or more and 94 mass% or less of thermoplastic resin (C) relative to the total mass (100 mass%) of the resin composition, and more preferably contain 3 mass% or more and 8 mass% or less of aromatic polysulfone (A), 13 mass% or more and 18 mass% or less of fluororesin (B), and 74 mass% or more and 84 mass% or less of thermoplastic resin (C).

[0138] In another aspect, the resin composition of the embodiment may preferably contain 1% by mass or more and 18% by mass or less of aromatic polysulfone (A), 5% by mass or more and 22% by mass or less of fluororesin (B), and 60% by mass or more and 94% by mass or less of thermoplastic resin (C), relative to the total amount of the aromatic polysulfone (A), the thermoplastic resin (C), and the fluororesin (B) being 100% by mass, or more preferably contain 3% by mass or more and 8% by mass or less of aromatic polysulfone (A), 13% by mass or more and 18% by mass or less of fluororesin (B), and 74% by mass or more and 84% by mass or less of thermoplastic resin (C).

[0139] <Optional ingredients> The resin composition of the embodiment may contain other optional components, as necessary, that do not fall under the category of the aromatic polysulfone (A), the thermoplastic resin (C), and the fluororesin (B), such as fillers such as fibrous fillers, plate-like fillers, spherical fillers, powdery fillers, irregularly shaped fillers, and whiskers, as well as colorants, lubricants, various surfactants, antioxidants, heat stabilizers, ultraviolet absorbers, and antistatic agents.

[0140] Examples of fibrous fillers include glass fiber, PAN-based carbon fiber, pitch-based carbon fiber, silica alumina fiber, silica fiber, alumina fiber, other ceramic fibers, liquid crystal polymer (LCP) fiber, aramid fiber, and polyethylene fiber. Examples of plate-like fillers include talc, mica, graphite, and wollastonite. Examples of spherical fillers include glass beads and glass balloons. Examples of powder fillers include calcium carbonate, dolomite, clay barium sulfate, titanium oxide, carbon black, conductive carbon, and fine silica. Examples of irregularly shaped fillers include glass flakes and irregular cross-section glass fibers. Examples of whiskers include wollastonite and potassium titanate fiber. In addition, optional components include solid lubricants such as molybdenum disulfide, heat-resistant resin particles such as oxybenzoyl polyester and polyimide, and colorants such as dyes and pigments. These optional components can be used alone or in combination of two or more. The content of these optional components is preferably 250 parts by mass or less, more preferably 150 parts by mass or less, even more preferably 100 parts by mass or less, and particularly preferably 67 parts by mass or less, per 100 parts by weight of the total amount of the aromatic polysulfone (A), the thermoplastic resin (C), and the fluororesin (B).

[0141] As described above, the resin composition of the embodiment containing the aromatic polysulfone (A), the fluororesin (B) and the thermoplastic resin (C) is very useful because it has improved fatigue resistance. The mechanism by which fatigue resistance is improved in the resin composition of the embodiment containing aromatic polysulfone (A), fluororesin (B), and thermoplastic resin (C) is not clear; however, it is believed that the action of aromatic polysulfone (A) finely disperses the fluororesin (B), suppressing stress concentration at the interface with the fluororesin (B), thereby improving fatigue test results.

[0142] (Fatigue resistance) The fatigue resistance of the resin composition of the embodiment can be evaluated using the number of times that the test piece is pulled until it breaks, as an index, as measured in the following [Fatigue Test]. The greater the number of times that the test piece is pulled, the better the fatigue resistance can be determined to be.

[0143] [Fatigue test] Using the resin composition as a molding material, an injection molding machine (for example, SE100EV-A model manufactured by Sumitomo Heavy Industries, Ltd.) is used to perform injection molding under the conditions of a cylinder temperature of 340 to 370°C, a mold temperature of 150°C, a back pressure of 10 MPa, a screw rotation speed of 80 rpm, a filling pressure of 150 MPa, a holding pressure of 80 MPa, and a cooling time of 25 seconds, to obtain a plate-shaped test piece (thickness: 2.5 mm) conforming to JIS K 7118. Figure 1 shows an example of the test piece, and shows a plan view of the test piece produced by the injection molding as seen from above, and its dimensions (unit: mm). The obtained test specimen is subjected to a tensile fatigue test in accordance with JIS K 7118 using a fatigue tester (e.g., "EHF-FB1" manufactured by Shimadzu Corporation) under conditions of a maximum stress of 40 MPa, a stress ratio of 0.2, a frequency of 10 Hz, a chuck distance of 50 mm, and a waveform of sine wave, in an atmosphere of a test temperature of 23°C and a relative humidity of 50%. The measurement is performed on two test specimens per resin composition, and the average number of times the test specimen is pulled until it breaks is used.

[0144] The number of times that the test piece is pulled until it breaks, as measured in the above-mentioned [Fatigue Test], using the resin composition of the embodiment as a measurement sample, may be 7,000 or more, or may be 7,000 or more and 30,000 or less, or may be 10,000 or more and 20,000 or less, or may be 12,000 or more and 15,000 or less.

[0145] [Method of producing resin composition] The resin composition of the embodiment can be obtained by mixing the above-mentioned aromatic polysulfone (A), thermoplastic resin (C), and fluororesin (B), as well as any optional components used as necessary, all at once or in a suitable order.

[0146] According to the method for producing a resin composition of the embodiment, it is possible to produce the resin composition of the above embodiment.

[0147] In the method for producing the resin composition, the aromatic polysulfone (A), the thermoplastic resin (C), the fluororesin (B), and optional components, as well as their blending ratios, can be exemplified by the same ones as those explained in the above “Resin Composition”.

[0148] A method for producing a resin composition according to an embodiment includes a step of mixing an aromatic polysulfone (A), a fluororesin (B), and a thermoplastic resin (C), and the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the fluororesin (B) has the following <CF 3 Measurement method for the content of CF 3 A method for producing a resin composition having a group content of less than 0.15% is exemplified. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Group content (%)={((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

[0149] In the method for producing a resin composition according to the embodiment, it is preferable that the aromatic polysulfone (A) is blended in an amount of 1 mass% or more and 18 mass% or less, and the fluororesin (B) is blended in an amount of 5 mass% or more and 22 mass% or less, relative to 100 mass% of the total mass of the resin composition.

[0150] In the method for producing a resin composition according to the embodiment, the thermoplastic resin (C) is preferably blended in an amount of 60% by mass or more and 94% by mass with respect to 100% by mass of the total mass of the resin composition.

[0151] The mixing is preferably melt kneading. The resin composition of the present embodiment can be provided as a pelletized product by melt kneading the aromatic polysulfone (A), the thermoplastic resin (C), the fluororesin (B), and any optional components used as required using an extruder. The melt kneading does not necessarily have to be performed using an extruder, and a Banbury mixer or rolls can also be used. Note that it is preferable to use a twin-screw kneading extruder as the extruder.

[0152] The resin composition thus obtained, particularly pellets of the resin composition, can be suitably used as a molding material for the molded article described below.

[0153] <Molded body> The molded article of the present embodiment is a molded article containing the resin composition of the above-mentioned embodiment. An example of the molded article of the present embodiment is a molded article made of the resin composition of the embodiment.

[0154] The molded article of the present embodiment includes an aromatic polysulfone (A) having a polar group and / or a salt thereof in the molecule, a fluororesin (B), and a thermoplastic resin (C) other than the aromatic polysulfone (A) and the fluororesin (B), and the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the fluororesin (B) has the following <CF 3 Measurement method for the content of CF 3 An example of such a molded article is one having a group content of less than 0.15%. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Group content (%)={((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

[0155] The molded article of the present embodiment can be obtained by a known molding method using the resin composition of the present embodiment. As a molding method of the resin composition of the present embodiment, a melt molding method is preferable, and examples thereof include an injection molding method, an extrusion molding method such as a T-die method or an inflation method, a compression molding method, a blow molding method, a vacuum molding method, and a press molding method, and an injection molding method is preferable.

[0156] An example of a method for producing a molded article according to the present embodiment is a method for producing a molded article that includes injection molding using the resin composition according to the above-described embodiment as a molding material.

[0157] For example, when the above-mentioned resin composition is used as a molding material and molded by injection molding, the resin composition is melted using a known injection molding machine, and the molten resin composition is injected into a mold to mold it. When the resin composition is charged into the injection molding machine, each component may be charged separately into the injection molding machine, or some or all of the components may be mixed in advance and then charged into the injection molding machine as a mixture.

[0158] The temperature conditions for injection molding are appropriately determined depending on the type of resin composition, and the cylinder temperature of the injection molding machine can be appropriately set depending on the melt viscosity of the resin composition used.

[0159] The temperature of the mold is preferably set within the range of room temperature (25° C.) to 180° C. in terms of the cooling rate of the resin composition and productivity. Other injection conditions such as the screw rotation speed, back pressure, injection speed, pressure holding, and pressure holding time may be appropriately adjusted.

[0160] The molded article of the present embodiment can be generally used in any application to which a resin composition can be applied. The molded article of the present embodiment can be used in a wide variety of applications, including electrical and electronic components such as connectors, sockets, IC sockets, burn-in sockets, relay parts, coil bobbins, optical pickups, oscillators, printed wiring boards, circuit boards, semiconductor packages, and computer-related parts; semiconductor manufacturing process-related parts such as IC trays and wafer carriers; home electrical product parts such as VTRs, televisions, irons, air conditioners, stereos, vacuum cleaners, refrigerators, rice cookers, and lighting fixtures; lighting fixture parts such as lamp reflectors and lamp holders; audio product parts such as compact discs, laser discs (registered trademark), and speakers; ferrules for optical cables, telephone parts, facsimile parts, and communication device parts such as modems; separation claws, heaters, etc. parts related to copiers and printers, such as motor holders; mechanical parts, such as impellers, fan gears, gears, bearings, motor parts and cases; automotive parts, such as automotive mechanism parts, engine parts, engine room parts, electrical parts, and interior parts; cooking utensils, such as microwave cooking pots and heat-resistant tableware; thermal insulation and soundproofing materials, such as flooring and wall materials, supporting materials, such as beams and pillars, building materials, or civil engineering and construction materials, such as roofing materials; aircraft, spacecraft, and space equipment parts; radiation facility parts, such as nuclear reactors, marine facility parts, cleaning tools, optical equipment parts, valves, pipes, nozzles, filters, membranes, medical equipment parts and materials, sensor parts, sanitary equipment, sporting goods, leisure goods, and cable ties.

[0161] The molded article of the embodiment has excellent fatigue resistance because the resin composition of the embodiment is used. The molded article of the embodiment can be suitably used as a part that requires fatigue resistance, such as a gear.

[0162] The gear of the present embodiment is a gear including the resin composition of the above-described embodiment, the resin composition including an aromatic polysulfone (A) having a polar group and / or a salt thereof in the molecule, a fluororesin (B), and a thermoplastic resin (C) other than the aromatic polysulfone (A) and the fluororesin (B), the content of the polar group and / or the salt thereof in the aromatic polysulfone (A) being 1×10 -5 mol / g or more 40×10 -5 mol / g or less, and the fluororesin (B) has the following <CF 3 Measurement method for the content of CF 3 The base content is less than 0.15%. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Group content (%)={((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

[0163] An example of the gear of the present embodiment is a gear made of the resin composition of the present embodiment. <1> ~ <9> The gear may include the resin composition according to any one of the above items.

[0164] The type of gear is not particularly limited, and examples thereof include spur gears, helical gears, racks, internal gears, worm gears, worm wheel gears, bevel gears, hypoid gears, and the like.

[0165] The gear of the present embodiment can be suitably used as a food contact gear. Examples of food contact gears include gears provided in food production devices or food production equipment. The food contact gear comes into contact with food or food ingredients directly or indirectly as a part of the device or equipment during the food production process. The food here includes food ingredients, food in the process of production, and finished food.

[0166] The gear of this embodiment can be suitably used as a gear for contacting a drug. Examples of gears for contacting a drug include gears provided in drug manufacturing devices or equipment. The gear for contacting a drug comes into contact with a drug or drug raw materials directly or indirectly as a part of the device or equipment during the drug manufacturing process. The drug here includes drug raw materials, drugs in the process of being manufactured, and completed drugs.

[0167] In the food contact gear or medicine contact gear of the embodiment, the total content of the aromatic polysulfone (A) and the aromatic polysulfone (c) may be 50 mass% or more, 61 mass% or more and 92 mass% or less, or 77 mass% or more and 87 mass% or less, relative to the total mass (100 mass%) of the resin composition.

[0168] Aromatic polysulfone is a highly biocompatible material that is also used for medical purposes, and therefore offers high safety even in the event that gear fragments are mixed into food, medicine, etc.

[0169] In another aspect, the present embodiment is <1> ~ <9> The present invention provides a food production device comprising a gear including the resin composition according to any one of the above items. In another aspect, the present embodiment is <1> ~ <9> The present invention provides a pharmaceutical manufacturing device comprising a gear including the resin composition according to any one of the above items.

[0170] Another aspect of the present embodiment is a food manufacturing method using a food manufacturing apparatus having a gear, the food manufacturing apparatus contacting food or food ingredients in a food manufacturing process, the gear comprising: <1> ~ <9> The present invention also provides a method for producing a food product, the food product being a gear comprising the resin composition according to any one of the above items.

[0171] Another aspect of the present embodiment is a method for producing a drug using a drug production apparatus having a gear, the method including contacting a drug or a drug raw material during the drug production process, the drug production apparatus comprising: <1> ~ <9> The present invention also provides a method for producing a pharmaceutical product, the pharmaceutical product being a gear comprising the resin composition according to any one of the above items. EXAMPLES

[0172] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0173] ≪Raw materials≫ <Aromatic polysulfone (A)> PES1 Polyethersulfone "Sumikaexcel 5003P" manufactured by Sumitomo Chemical Co., Ltd. was used (hereinafter abbreviated as "PES1"). The repeating unit of this PES1 is represented by the formula (1) above. 1 and Ph 2 are repeating units each of which is a p-phenylene group, and the terminal groups contain hydroxyl groups. The content of hydroxyl groups per gram of aromatic polysulfone measured by the measurement method described below is 8.6 × 10 -5 mol / g and the reduced viscosity is 0.51 dL / g.

[0174] <Thermoplastic resin (C)> PES2 Polyethersulfone "Sumikaexcel 4100P" manufactured by Sumitomo Chemical Co., Ltd. was used (hereinafter abbreviated as "PES2"). The repeating unit of this PES2 is represented by the formula (1) above. 1 and Ph 2are repeating units each of which is a p-phenylene group, the terminal group contains a chloro group, and the content of hydroxyl groups per gram of aromatic polysulfone measured by the measurement method described below is 1.8 × 10 -6 mol / g and the reduced viscosity is 0.41 dL / g.

[0175] <Fluororesin> Resin F1 In a 36 L stainless steel autoclave equipped with an agitator, 21.8 kg of deionized water, 50 g of ammonium carbonate buffer, and perfluoroalkyl (C 4 ~C 16 ) mixture of ammonium ethanesulfonate (average C 8 The autoclave was closed, evacuated, then sparged with tetrafluoroethylene (TFE) three times and evacuated again. Ethane was introduced into the autoclave until the pressure rose to 16.9 kPa, after which 44.95 mL of perfluoro(propyl vinyl ether) (PPVE) and Freon® F-113 (CCl 2 FCC 2 ) 350 mL was pumped into the autoclave. The autoclave was pressurized to 2.1 MPa with TFE and at the same time a solution of 1.5 g ammonium persulfate (APS) in 500 mL deionized water was pumped into the autoclave. After the polymerization had started (pressure drop of 0.07 MPa), additional PPVE and a solution of 1.2 g APS in 1000 mL deionized water were pumped into the autoclave at rates of 1.10 mL / min and 10 mL / min, respectively, relative to the residue of the polymerization. The stirrer speed was adjusted to regulate the reaction such that an additional 50 g TFE per minute was required to keep the pressure constant at 2.2 MPa. After adding 7 kg TFE from the start of the reaction, the TFE and PPVE feeds and the stirrer were stopped. The initiator solution (APS) was pumped continuously until the unreacted material was discharged from the autoclave. The coagulated polymer was removed from the autoclave, washed with deionized water, and dried at 150° C. to obtain a fluororesin (resin F1).

[0176] Resin F2 Perfluoro(propyl vinyl ether) (PPVE) and Freon® F-113 (CCl) were injected into the autoclave before the reaction started. 2 FCC 2 The injection volume was 44.85 mL of perfluoro(propyl vinyl ether) (PPVE) and 44.85 mL of Freon® F-113 (CCl 2 FCC 2 A fluororesin (resin F2) was obtained in the same manner as for resin F1, except that the amount of reaction mixture was changed to 350 mL.

[0177] The resins F1 and F2 obtained above were subjected to CF 3 The group contents were measured and the results are shown in Tables 1-4.

[0178] <Measurement> [Hydroxyl group content of aromatic polysulfone] A predetermined amount of aromatic polysulfone was dissolved in dimethylformamide, and an excess amount of paratoluenesulfonic acid was added. The solution was then titrated with 0.05 mol / L potassium methoxide / toluene-methanol solution (volume ratio of toluene:methanol = 8:2) using a potentiometric titrator to neutralize the remaining paratoluenesulfonic acid and then the hydroxyl groups were neutralized. The amount (mol) of potassium methoxide required to neutralize the hydroxyl groups was divided by the predetermined amount (g) of aromatic polysulfone to determine the content of the hydroxyl groups in the aromatic polysulfone.

[0179] [Reduced viscosity of aromatic polysulfone] Approximately 1 g of aromatic polysulfone was dissolved in N,N-dimethylformamide to a volume of 1 dL, and the viscosity (η) of this solution was measured at 25°C using an Ostwald-type viscosity tube. The viscosity (η) of the solvent, N,N-dimethylformamide, was also measured. 0 The viscosity of the solution (η) and the viscosity of the solvent (η) were measured at 25°C using an Ostwald-type viscometer. 0 ) and the specific viscosity ((η-η 0 ) / η 0The reduced viscosity (dL / g) of the aromatic polysulfone was calculated by dividing the viscosity (dL) by the concentration of the solution (about 1 g / dL).

[0180] [CF in fluororesin 3 Measurement of group content] CF in resins F1-F2 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, CF 2 Peak area corresponding to group ICF 2 Therefore, it was calculated using the following formula (f1). CF 3 Group content (%)={((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

[0181] CF 3 The base content was calculated 19 F solid-state NMR measurements were performed by the single pulse method under the following conditions.

[0182] Spectrometer: JNM-ECZL600G (manufactured by JEOL RESONANCE) Static magnetic field strength: 14.1 Tesla (resonance frequency at 1H: 600MHz) Observed nucleus: 19F (resonance frequency 565MHz) Measurement method: Single pulse method MAS condition: 16kHz (PTFE (Fluon L169J) was also measured at 20kHz) Wait time: 15 seconds Number of measurements: 128 (=27, measurement time approx. 32 minutes) Measurement temperature: Room temperature (actual value 23°C) Reference material: PTFE (set to -122 ppm)

[0183] <Production of resin composition> [Examples 1 to 6, Comparative Examples 1 to 7] <Preparation of pellets> The raw materials shown in Tables 1 to 4 were mixed in the proportions (mass%) shown in Tables 1 to 4 using a Henschel mixer, and then melt-kneaded using a twin-screw extruder ("PCM-30" manufactured by Ikegai Iron Works Co., Ltd.) under conditions of a cylinder temperature of 300 to 350°C and a screw rotation speed of 150 rpm. The mixture was discharged in the form of strands through a circular nozzle (discharge port) with a diameter of 3 mm, passed through a water bath with a water temperature of 30°C for 1.5 seconds, passed through a roller, and pelletized with a strand cutter (manufactured by Tanabe Plastics Machinery Co., Ltd.) with a rotating blade adjusted to 20 m / min, thereby obtaining the resin compositions of each Example and Comparative Example in the form of pellets.

[0184] <Molding> Pellets of each resin composition were used as molding materials and dried at 150°C for 12 hours using a hot air circulating dryer. Plate-shaped test pieces (thickness: 2.5 mm) conforming to JIS K 7118 were then injection molded using an injection molding machine (SE100EV-A type, manufactured by Sumitomo Heavy Industries, Ltd.). The injection molding conditions were: cylinder temperature 340-370°C, mold temperature 150°C, back pressure 10 MPa, screw rotation speed 80 rpm, filling pressure 150 MPa, holding pressure 80 MPa, and cooling time 25 seconds. A plan view of the test piece produced by the injection molding as seen from above and its dimensions (unit: mm) are shown in Figure 1.

[0185] Evaluation The fatigue resistance of the resin composition was evaluated using the number of times that the test piece was pulled until it broke, as an index, as measured on the test piece in the "Fatigue Test" described below. The more the number of times that the test piece was pulled, the better the fatigue resistance can be determined to be.

[0186] [Fatigue test] The test pieces produced above were subjected to a tensile fatigue test in accordance with JIS K 7118 using a fatigue testing machine (Shimadzu Corporation, "EHF-FB1") under the following conditions: test temperature 23°C, relative humidity 50%, stress mode: tension, maximum stress 40 MPa, stress ratio 0.2, frequency 10 Hz, test speed 1 / 10 sec, chuck distance 50 mm, waveform: sine wave. The measurement was carried out on two test pieces for each example, and the number of times the test pieces were pulled until they broke was counted and the average value was calculated. The stress ratio is the ratio of the minimum stress to the maximum stress in one cycle of repeated loading.

[0187] The above measurement results are shown in Tables 1 to 4.

[0188] [Table 1]

[0189] Referring to Table 1, a comparison between Comparative Examples 1 to 3, which contain only PES2 (thermoplastic resin (C)) and resin F1 (fluororesin (B)) and do not contain PES1 (aromatic polysulfone (A)), and Examples 1 to 3, which contain PES1, confirmed that Examples 1 to 3, which contain PES1, showed significantly improved fatigue test results.

[0190] [Table 2]

[0191] [Table 3]

[0192] On the other hand, referring to Table 2, when resin F2 was contained instead of resin F1, even in Comparative Example 4 which contained PES1 (aromatic polysulfone (A)), no significant improvement in the fatigue test results was observed as in Example 2 compared to Comparative Example 5 which did not contain PES1.

[0193] Similarly, referring to Table 3, when resin F2 was contained instead of resin F1, even in Comparative Example 6 which contained PES1 (aromatic polysulfone (A)), no significant improvement in the fatigue test results was observed as in Example 3 compared to Comparative Example 7 which did not contain PES1.

[0194] From the above, it is assumed that the hydroxyl group content is 1×10 -5mol / g or more 40×10 -5 A specific aromatic polysulfone (A) having a value of mol / g or less and CF 3 It was shown that a combination with a specific fluororesin (B) having a group content of less than 0.15% resulted in an unexpected improvement in fatigue resistance.

[0195] [Table 4]

[0196] The results when the content of Resin F1 was fixed at 15 mass% and the content ratio of PES1 to PES2 was changed are shown in Table 4. Compared to Comparative Example 2 which did not contain PES1 (aromatic polysulfone (A)), all of Examples 2 and 4 to 6 which contained PES1 showed a remarkable improvement in fatigue test results.

[0197] [Dispersion state of PTFE] Among the test pieces produced above, the test pieces molded from the resin compositions of Example 2, Comparative Example 2, Comparative Example 4, and Comparative Example 5 were cut in the center, the cut surface was polished with a polishing machine ("Refine Polisher" manufactured by Kasai Shoko Co., Ltd.), gold was evaporated using a gold evaporation device ("Ion Sputter E101" manufactured by Hitachi, Ltd.), and an SEM observation image of the cross section of the test piece was obtained (magnification 1000 times) using a scanning electron microscope (SEM, S-2300 type, Hitachi scanning electron microscope). The results are shown in FIG. 2.

[0198] The SEM observation image of the cross section of the test piece obtained above was binarized into the continuous phase region and the PTFE region scattered as aggregates using image analysis software ("WinROOF" Ver.3.54, manufactured by Mitani Shoji Co., Ltd.) The white island-like regions observed in Figure 2 are the PTFE regions. The threshold value for the binarization process may be set to a value that allows the PTFE to be distinguished from other components by visually checking the image. Using the binarized image, we removed dust and noise that was clearly not PTFE, and areas of PTFE cut off in the middle of the image edge, and then calculated the circle-equivalent diameter of PTFE. The circle-equivalent diameter is the diameter of a PTFE of the same area converted into a perfect circle. The image was made to contain more than 100 PTFE areas, and the average particle size was calculated from the arithmetic mean of the circle-equivalent diameters.

[0199] Comparison of Example 2 and Comparative Example 2: When Resin F1 was contained, the test piece of Example 2 containing PES1 (aromatic polysulfone (A)) had finely dispersed PTFE compared to the test piece of Comparative Example 2 not containing PES1. That is, the test piece of Example 2 and the test piece of Comparative Example 2 had a significantly different dispersed state of PTFE.

[0200] The average particle size of PTFE calculated from the arithmetic mean of the equivalent circle diameter was as follows: Average particle size of PTFE in Example 2: 6.94 μm Average particle size of PTFE in Comparative Example 2: 18.27 μm

[0201] In addition, the statistics of the circular equivalent diameter of PTFE were as follows: First quartile of the distribution of circular equivalent diameters of PTFE in Example 2: 4.51 μm The third quartile of the distribution of the equivalent circular diameter of PTFE in Example 2: 8.13 μm First quartile of the distribution of circular equivalent diameters of PTFE in Comparative Example 2: 7.81 μm The third quartile of the distribution of the equivalent circular diameter of PTFE in Comparative Example 2: 24.54 μm As can be seen from Table 1, the test piece of Example 2 was far superior in fatigue resistance to the test piece of Comparative Example 2.

[0202] In FIG. 2, it can be seen that the test piece molded from the resin composition of Example 2 to which the present invention is applied is a molded product 100 having a continuous phase 10 and a dispersed phase 20 dispersed in the continuous phase 10, where the continuous phase 10 is composed of a phase containing PES1 (aromatic polysulfone (A)) and PES2 (thermoplastic resin (C)), and the dispersed phase 20 is molded product 100 composed of a particle group containing resin F1 (fluororesin (B)). The particle group has an average particle size of 4.94 to 8.94 μm. The interquartile range of the equivalent circle diameter for the particle group is 1.62 to 5.62 μm.

[0203] The first quartile of the equivalent circle diameter for the particle group is preferably 3.51 to 5.51 μm.The third quartile of the equivalent circle diameter for the particle group is preferably 6.13 to 10.13 μm.

[0204] On the other hand, when Resin F2 was contained instead of Resin F1, no significant change was observed in the dispersion state of PTFE between the test piece of Comparative Example 4 containing PES1 (aromatic polysulfone (A)) and the test piece of Comparative Example 5 not containing PES1, and the fatigue resistance was inferior to that of the test piece of Example 2.

[0205] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims. [Explanation of symbols]

[0206] 10 continuous phase, 20 dispersed phase, 100 compact

Claims

1. An aromatic polysulfone (A) having a polar group and / or a salt thereof in the molecule; A fluororesin (B), and a thermoplastic resin (C) other than the aromatic polysulfone (A) and the fluororesin (B), The content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, In the fluororesin (B), 3 Measurement method for CF group content 3 The resin composition has a group content of less than 0.15%. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, C.F. 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Base content (%) = {((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

2. The resin composition according to claim 1, wherein the thermoplastic resin (C) is an aromatic polysulfone (c) that does not fall under the aromatic polysulfone (A).

3. The resin composition according to claim 2 , wherein the aromatic polysulfone (c) has a repeating unit represented by the following formula (1): (1)-Ph 1 -SO 2 -Ph 2 -O- [In the formula, Ph 1 and Ph 2 each independently represents a phenylene group. A hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group, a halogen atom, a sulfo group, a nitro group, an amino group, a carboxyl group, or a hydroxyl group.

4. The resin composition according to any one of claims 1 to 3, wherein the polar group of the aromatic polysulfone (A) is a hydroxyl group and / or an amino group.

5. The resin composition according to any one of claims 1 to 3, wherein the aromatic polysulfone (A) has a repeating unit represented by the following formula (1): (1)-Ph 1 -SO 2 -Ph 2 -O- [In the formula, Ph 1 and Ph 2 each independently represents a phenylene group. A hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group, a halogen atom, a sulfo group, a nitro group, an amino group, a carboxyl group, or a hydroxyl group.

6. The <CF 3 Measurement method for CF group content 3 The resin composition according to any one of claims 1 to 3, wherein the group content is 0.11% or less.

7. The resin composition according to any one of claims 1 to 3, wherein the fluororesin (B) is polytetrafluoroethylene (PTFE).

8. The resin composition according to any one of claims 1 to 3, wherein the content of the aromatic polysulfone (A) is 1 mass% or more and 18 mass% or less, and the content of the fluororesin (B) is 5 mass% or more and 22 mass% or less, relative to 100 mass% of the total mass of the resin composition.

9. The resin composition according to any one of claims 1 to 3, wherein the content of the thermoplastic resin (C) is 60% by mass or more and 94% by mass or less with respect to 100% by mass of the total mass of the resin composition.

10. A molded article comprising the resin composition according to any one of claims 1 to 3.

11. A gear comprising the resin composition according to any one of claims 1 to 3.

12. 12. The gear of claim 11, which is a food contact gear.

13. 12. The gear of claim 11 which is a pharmaceutical contact gear.

14. A method for producing the resin composition according to any one of claims 1 to 3, An aromatic polysulfone (A) having a polar group and / or a salt thereof in the molecule; A fluororesin (B), The method includes a step of mixing the aromatic polysulfone (A) and a thermoplastic resin (C) other than the fluororesin (B), The content of the polar group and / or the salt thereof in the aromatic polysulfone (A) is 1×10 -5 mol / g or more 40×10 -5 mol / g or less, In the fluororesin (B), 3 Measurement method for CF group content 3 The method for producing a resin composition, wherein the resin composition has a carboxyl group content of less than 0.15%. <CF 3 Method for measuring base content> CF in the fluororesin (B) 2 CF vs. group content 3 The group content is 19 CF measured by F solid-state NMR 3 Peak area corresponding to group ICF 3 And, C.F. 2 Peak area corresponding to group ICF 2 Therefore, it is calculated by the following formula (f1). CF 3 Base content (%) = {((ICF 3 ) / 3) / ((ICF 2 ) / 2)}×100 (f1)

Citation Information

Patent Citations

  • Gas pressure welding device of rail

    JP1980064986A